Síntese e caracterização de nanofios de óxido de cobre produzidos por termo-oxidação - Amorim, Allan Miguel Franco de (2020)
The study of the development of nanostructured semiconductor materials is responsible for a considerable portion of tectonological advances in recent years. Nanowires, in particular, offer unique opportunities to control electronic and optical properties in semiconductors. In this context, the present work investigated the formation of copper oxide nanowires through the oxidation process of metallic copper sheets and how the synthesis conditions influence the concentration and structure of the oxides. For that, X-ray diffraction (XRD) and scanning electron microscopy (SEM) characterizations were performed. The nanowire synthesis process was first evaluated in the treatment of metallic copper sheets before the oxidation process and then in the thermal process performed in atmospheric environment. Two treatment procedures were investigated, namely: immersion in chloridric acid solution followed by immersion in ethanol in ultrasound; and immersion in acetone followed by immersion in isopropyl alcohol in ultrasound. It is concluded that the treatment with hydrochloric acid solution and ethanol is effective in promoting a porous medium on the metal surface that improves the number of active sites for the oxidation of copper ions and, consequently, promotes a more uniform growth of the oxides.After selecting the best pre-treatment, the thermal process was evaluated through a 33 factorial experimental design using as parameters: the temperature (400-700 °C), the heating rate up to the threshold temperature (5-15 ° C/min) and process duration (3-9 hours). The samples were analyzed for the presence of nanowire structures and its diameters. Crystalline structures were identified as oxide copper I and II (CuO and Cu2O) in addition to metallic copper in all tests performed. The nanowires have diameters that vary between 60 and 120 nm. The analysis of variance (ANOVA) for the factorial design tests 33 indicated, with a 95% reliability level, that the temperature and the heating rate had an influence on the concentration and the average diameter of the nanostructures obtained.